Exploring Marketing Knowledge, Entrepreneurial Orientation, and Product Innovation on Marketing Performance of Pastry MSME - Komaryatin, Nurul; Arifin, Samsul; Ali, Ali; Huda, Nurul; Roosdhani, Mohamad Rifqy (Jurnal Entrepreneur dan Entrepreneurship, 2025)
The performance of Micro, Small, and Medium-Sized Enterprises (MSMEs) must be enhanced to facilitate their rapid growth and increase their contribution to the economy. A key factor influencing the advancement of MSMEs is their performance. To improve marketing effectiveness, MSMEs must adopt the most suitable marketing strategies for each of their products. Through effective marketing performance, businesses can identify challenges that may affect their competitiveness and long-term sustainability. This study aims to explore the role of product innovation, entrepreneurial orientation, and marketing expertise in enhancing the marketing performance of MSMEs. A purposive sampling method was employed to select 96 active MSMEs in the pastry industry in Bugo Village, Welahan, Jepara Regency. Data analysis was conducted using multiple regression analysis. The results indicate that product innovation, entrepreneurial orientation, and marketing expertise have significant and positive effects on marketing success. The findings suggest that strengthening product innovation, entrepreneurial mindset, and marketing knowledge can further improve marketing performance in MSMEs, particularly in the pastry industry.